Calculating Confidence Interval Estimation Using Maximum Likelihood Estimator For Dataset - Mokhtar, Siti Fairus; Zahayu, Md Yusof; Hasimah, Sapiri (Universiti Sultan Zainal Abidin, 2021)
Confidence interval estimation is an important technique in statistical inference. The objective of this paper is to demonstrate the calculation of confidence interval using maximum likelihood method for surface roughness. The advantages of maximum likelihood method are convenience to use and computational efficient. The interval length of confidence interval showed that 99% is the highest width compared to 90% and 95%